Environmental Sustainability - Environmental Sustainability (Springer Nature, 2026)
Environmental Sustainability is a multi-disciplinary, quarterly, peer reviewed journal focused at maintaining and sustaining the quality of our planet through biological and eco-friendly methods. The journal will cover original research articles, short communication, reviews, mini reviews and scientific opinions/commentaries in the field of Environmental Science, Microbiology, Biotechnology, Biochemistry, and Agriculture Sciences which report findings related to sustenance and remediation of ecosystems.  The journal will target contemporary issues such as biodegradation, bioremediation, reclamation of barren/ stress systems, combating climate change, green fuels, sustainable agriculture, organic food production, etc. This journal is published by ‘Society for Environmental Sustainability’.
FI 0.27
Q2
Keywords: Earth; Space & Environmental Sciences; Sustainable Development; Acuerdos transformativos; Transformative agreements; Sostenibilidad ambiental; Biorremediación; Agricultura sostenible; Biotecnología ambiental; Biodegradación; Microbiología ambiental